The life of Thomas Harrison, Major-General in the army of the commonwealth of England, and one of the judges of King Charles I (Hamilton, 1893)
Repr.: Proceedings of the American antiquarian society, at the Semi-Annual Meetin, April 26, 1893. Expansian of first publ. in the Dictionary of national biography.